2018
DOI: 10.1186/s12941-018-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Nasal colonization with methicillin-resistant Staphylococcus aureus among elderly living in nursing homes in Brazil: risk factors and molecular epidemiology

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus poses a threat to elderly living in nursing homes. Studies focusing on the epidemiology of colonization may help in the design of infection control strategies.ObjectiveTo identify factors associated with MRSA colonization and the dissemination of clones among nursing home residents.MethodsNasal swabs were collected from 300 persons from nine nursing homes in the city of Bauru, Brazil. Resistance to methicillin was identified through amplification of the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
15
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
10
15
3
Order By: Relevance
“…MRSA was rare among community-dwellers (0.4%), similar to investigations in other parts of Germany [37]. The prevalence was also rather low among nursing home residents compared with other surveys, where carriage rates ranged from 3.7% and 5.5% in Brazilian and German long-term care facilities to 15.7% in Spanish and 17.2% in Italian nursing homes [3943]. The assessment of risk factors for colonization had been a further objective of this study.…”
Section: Discussionsupporting
confidence: 78%
“…MRSA was rare among community-dwellers (0.4%), similar to investigations in other parts of Germany [37]. The prevalence was also rather low among nursing home residents compared with other surveys, where carriage rates ranged from 3.7% and 5.5% in Brazilian and German long-term care facilities to 15.7% in Spanish and 17.2% in Italian nursing homes [3943]. The assessment of risk factors for colonization had been a further objective of this study.…”
Section: Discussionsupporting
confidence: 78%
“…However, SCCmec types I and II were also detected, which are commonly found circulating in health services. This fact has also been reported by Pereira-Franchi et al [62] and Silveira et al [69] who found a higher prevalence of isolates harboring SCCmec type II, which was attributed to a history of hospitalization.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth mentioning that patients in hospital-community settings, such as bedridden or institutionalized older adults with chronic infections, have a higher prevalence of SCCmec types I and II [62,69]; in addition, hospitalized patients frequently carry isolates that harbor SCCmec type III. These SCCmec are larger and carry plasmids and transposons with other resistance genes, often multidrug-resistant genes.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with the similar results regarding lack of relationship between S. aureus colonization and clinical conditions of hemodialysis patients such as diabetes and Hypertension [12, 14]. In the present study, MRSA colonization was independent of age consistent with similar studies [17, 18].…”
Section: Discussionsupporting
confidence: 94%